2017
DOI: 10.1007/s10533-017-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of phytoplankton-derived dissolved and particulate organic carbon in a highly eutrophic tropical coastal embayment (Guanabara Bay, Rio de Janeiro, Brazil)

Abstract: We investigate the carbon dynamics in Guanabara Bay, an eutrophic tropical coastal embayment surrounded by the megacity of Rio de Janeiro (southeast coast of Brazil). Nine sampling campaigns were conducted for dissolved, particulate and total organic carbon (DOC, POC and TOC), dissolved inorganic carbon (DIC), partial pressure of CO 2 (pCO 2 ), chlorophyll a (Chl a), pheo-pigments and ancillary parameters. Highest DOC, POC and Chl a concentrations were found in confined-shallow regions of the bay during the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
7
0
1
Order By: Relevance
“…Because information on the flow of inorganic and organic carbon in urbanized coastal waters is increasingly being reported, the impacts of human activities on coastal waters are becoming clearer. However, few studies have estimated carbon cycling and budget in highly urbanized coastal waters 17 . Carbon cycling in coastal ecosystems is increasingly subject to human influences, such as land and water use changes and increased waste and pollution 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Because information on the flow of inorganic and organic carbon in urbanized coastal waters is increasingly being reported, the impacts of human activities on coastal waters are becoming clearer. However, few studies have estimated carbon cycling and budget in highly urbanized coastal waters 17 . Carbon cycling in coastal ecosystems is increasingly subject to human influences, such as land and water use changes and increased waste and pollution 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The matrix correlation (Table S2) shows that higher values of δ 13 C-DIC are related to high levels of DO, POC, SPM, and Chl a, and low concentrations of DIC. Recent findings in Guanabara Bay showed that the DOC and POC fractions present a large phytoplankton dominance, surpassing the contribution of terrestrial sources (Cotovicz et al 2018a). Compared to other estuaries, Guanabara Bay presented the highest enrichment of 13 C-DIC in the salinity range between 20 and 30 ( Fig.…”
Section: Comparison With Other Ecosystems Worldwidementioning
confidence: 88%
“…The bay is one of the most polluted coastal systems in the world that receives large inputs of untreated domestic and industrial effluents at approximately 25 m 3 s −1 (Kjerfve et al, 1997;Bidone and Lacerda, 2004). We compartmentalized the bay into five domains (sectors 1, 2, 3, 4, and 5) as described by Cotovicz et al (2015;2018a) for the treatment, computations and interpretation of the data (Fig. 1).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Valores elevados relacionados a essas variáveis contribuem para o crescimento excessivo de macrófitas aquáticas aderidas que podem interferir na navegação, aeração e capacidade de transporte pelo canal. Desse modo, tais indicadores possibilitam a classificação dos corpos aquáticos em diferentes graus de trofia, ou seja, permitem avaliar a qualidade da água quanto ao enriquecimento por nutrientes e seu efeito relacionado ao crescimento excessivo das algas, ou o potencial para a proliferação desses organismos fotossintetizantes (Cotovicz et al, 2017).…”
Section: íNdice De Estado Tróficounclassified